Analysis of the Effectiveness of Key Instruments of the Vocational Rehabilitation System - Skiba, Wojciech (Studia Oeconomica Posnaniensia, 2019)
The article analyzes the problem of costal and social effectiveness of key social policy instruments in the field of vocational rehabilitation: wage subsidies for employing people with disabilities and payments to PFRON for not employing specific amounts of disabled employees. The basic method on the basis of which this goal is to be achieved is a multidimensional analysis of existing data, in particular official data from PFRON registers regarding subsidizing employment, employment as part of meeting the statutory minimum level of employment of disabled people and data on the professional activity of people with a disability from cyclical surveys of the professional activity of the population. The analysis covered the years 2008-2017, in some areas expanding the time perspective until 2004. The highest value of the article is to demonstrate, thanks to the innovative scope of analysis of official data, statistically significant deficiencies in the relationship between the analyzed key instruments of social policy and the employment level of people with disabilities.